5v-(-27)=97

Simple and best practice solution for 5v-(-27)=97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5v-(-27)=97 equation:


Simplifying
5v + -1(-27) = 97

Multiply -1 * -27
5v + 27 = 97

Reorder the terms:
27 + 5v = 97

Solving
27 + 5v = 97

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 5v = 97 + -27

Combine like terms: 27 + -27 = 0
0 + 5v = 97 + -27
5v = 97 + -27

Combine like terms: 97 + -27 = 70
5v = 70

Divide each side by '5'.
v = 14

Simplifying
v = 14

See similar equations:

| 56x^2y-21xy^2= | | m^3+5m^3-9m-45=0 | | 2x^2+2y^2=72 | | 2x^2=4-2x | | 4x-5=-5+7x | | -52+-26a=208 | | 22-2t=8 | | b=512 | | 3(5.33+6)+15(5.33)= | | (6-x)+(7-x)-(4-x)=0 | | 18=-12(7x-2) | | 3.98(x-15)-2.20x=107.62 | | 4x^3-2x+2=0 | | 10-7(6-5x)=4(6-x)-10x | | 3.98(x-15)-2.20=107.62 | | 3(n+6)+15n=114 | | -7-5=-2+x | | 2+2s=4 | | 16=5-5x | | 36x+67=468 | | 4+2z=20 | | 35*5+.10m=25.5+.25m | | 36x+67= | | 3(n+6)+15n= | | 72n^4-120n^2+50=0 | | 10-4p+28=2-2p | | 9t-6-6t=g | | 2=10-2g | | T=4*3.14*y | | .9(5x+10)=1.6-(x-2) | | 6-x=14 | | (3x+5)(2x^2-17x+35)=0 |

Equations solver categories